Predictors of Comorbid Conditions in Women Who Carry an FMR1 Premutation - Allen, Emily Graves; Charen, Krista; Hipp, Heather S.; Shubeck, Lisa; Amin, Ashima; He, Weiya; Hunter, Jessica Ezzell; Shelly, Katharine E.; Sherman, Stephanie L. (Frontiers in Psychiatry, 2021)
Purpose: Women who carry an FMR1 premutation can experience two well-established premutation-associated disorders: fragile X-associated primary ovarian insufficiency (FXPOI, affects ~20-30% carriers) and fragile X-associated tremor-ataxia syndrome (FXTAS, affects ~6-15% carriers); however, emerging evidence indicates that some of these women experience complex health profiles beyond FXPOI and FXTAS. Methods: In an effort to better understand predictors for these comorbid conditions, we collected self-reported medical histories on 413 women who carry an FMR1 premutation. Results: There were 22 health conditions reported by at least 9% of women. In an exploratory analysis, 12 variables were tested in logistic regression models for each comorbid condition, including demographic variables, environmental variables, premutation-associated factors, and endorsement of depression and/or anxiety. More than half of the comorbid conditions studied were associated with women who self-reported having anxiety. Age, smoking, body mass index (BMI), and depression were also significant predictor variables for specific comorbid conditions. Conclusions: Age, smoking and BMI were significantly associated with a subset of the comorbid conditions analyzed. Importantly, depression or anxiety were also significantly associated with many of the comorbid health conditions. This work highlights some of the modifiable factors associated with complex health profiles among women with an FMR1 premutation.